2011
DOI: 10.4314/njbas.v19i1.69362
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ipomea asarifolia</i> (Desr), A Potential Cover Crop for Soil Fertility Improvement in The Sudan Savanna Region, Nigeria

Abstract: ABSTRACT:The effect of Ipomea asarifolia on physico -chemical properties of the soils at Usmanu Danfodiyo University, Sokoto main campus, in the Sudan Savanna of Nigeria was investigated. The study determined the effect of the plant on some physical and chemical properties of soils, found out the nutrient retention ability of the plant in the soils and the variation of the effect with distance within the plants canopy. A total of 48 samples were collected from four different sites within Usmanu Danfodiyo Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This agrees with the result of Abdullahi et al (2011), who reported high Values are expressed as mean ± standard error of means based on six replicates. Means in a column followed by same letter(s) are not significantly different (Ns), * = significant (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with the result of Abdullahi et al (2011), who reported high Values are expressed as mean ± standard error of means based on six replicates. Means in a column followed by same letter(s) are not significantly different (Ns), * = significant (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…The significant (P< 0.05) decrease in sand and increase in clay proportions coupled with high though not significant increase in silt in I. asarifolia inhabited soil are attributable to its thick vegetation cover. Presence of the Ipomoea cover in soil has been reported in several researches (Aliero and Anka, 2001;Mazza, 2006 andAbdullahi et al, 2011) to provide effective protection against erosion due to the binding ability of the rhizoids in the root system, in addition to its firmly rooted shoot networks, which are not easily displaced by the forces of wind and water erosion.…”
Section: Discussionmentioning
confidence: 95%
“…The research area (upland and lowland) are located at about ten kilometers north of Sokoto metropolis. Sokoto State lies on an altitude of 308 m above sea level, within the Sudan savanna belt [10,11]. The climate is a hot semiarid type and characterized by long dry season from October to May and short rainy season from June to September, with an annual mean rainfall of 724mm for a period of six years [11,12].…”
Section: Study Site and Locationsmentioning
confidence: 99%
“…
In recent years a lot of attention has been drawn to the possibility of using cover crops, intercrops and mulch in the cultivation of different plant species (Univer et al 2009, Borowy 2013, Patkowska and Konopiński 2014a. They can have a positive effect on the microbiological activity of the soil and they enrich the soil with organic substances in addition to reducing weed infestation (Abdullahi et al 2011, Patkowska and Konopiński 2013a,b, Orzech and Wanic 2014, Patkowska and Błażewicz-Woźniak 2014. Moreover, they increase the population of soil-borne antagonistic microorganisms, which has a positive effect on the health of the cultivated plants Konopiński 2013c, Patkowska et al 2015).Ant agoni stic b ac ter i a B acillu s spp.
…”
mentioning
confidence: 99%